Cisplatin Promotes the Efficacy of Immune Checkpoint Inhibitor Therapy by Inducing Ferroptosis and Activating Neutrophils - Zhou, Ziwei; Zhao, Yiming; Chen, Si; Cui, Guohui; Fu, Wenkui; Li, Shouying; Lin, Xiaorong; Hu, Hai (Frontiers in Pharmacology, 2022)
The combination of immunotherapy with platinum-based chemotherapy has become the first-line treatment for patients with advanced non-small-cell lung cancer (NSCLC) with negative driver gene mutations. However, finding an ideal chemotherapeutic regimen for immunotherapy and exploring the underlying mechanism have noticeably attracted clinicians’ attention. In this study, we found that cisplatin induced ferroptosis of tumors cells, followed by N1 neutrophil polarization in the tumor microenvironment, which in turn remodeled the “cold” tumor to “hot” one through enhancing T cell infiltration and Th1 differentiation. Based on the important role of tumor ferroptosis in the immune-promoting effect of cisplatin, we noticed that the combination of a ferroptosis activator showed a synergistic effect with chemoimmunotherapy of epidermal growth factor receptor (EGFR)-mutant NSCLC, which would be an effective strategy to overcome immunotherapy resistance in NSCLC patients harboring driver mutations.